Selected Contribution: Airway caliber in healthy and asthmatic subjects: effects of bronchial challenge and deep inspirations - Jensen, Andrew; Atileh, Haytham; Suki, Bela; Ingenito, Edward P.; Lutchen, Kenneth R. (Journal of applied physiology (1985), 2001)
In 9 healthy and 14 asthmatic subjects before and after a standard bronchial challenge and a modified [deep inspiration (DI), inhibited] bronchial challenge and after albuterol, we tracked airway caliber by synthesizing a method to measure airway resistance (Raw; i.e., lung resistance at 8 Hz) in real time. We determined the minimum Raw achievable during a DI to total lung capacity and the subsequent dynamics of Raw after exhalation and resumption of tidal breathing. Results showed that even after a bronchial challenge healthy subjects can dilate airways maximally, and the dilation caused by a single DI takes several breaths to return to baseline. In contrast, at baseline, asthmatic subjects cannot maximally dilate their airways, and this worsens considerably postconstriction. Moreover, after a DI, the dilation that does occur in airway caliber in asthmatic subjects constricts back to baseline much faster (often after a single breath). After albuterol, asthmatic subjects could dilate airways much closer to levels of those of healthy subjects. These data suggest that the asthmatic smooth muscle resides in a stiffer biological state compared with the stimulated healthy smooth muscle, and inhibiting a DI in healthy subjects cannot mimic this.